Impacts of performance feedback on job satisfaction and job performance in the audit environment: The role of organizational justice and task complexity - Ho, My Hang (H. : ĐHQGHN, 2020)
This study will only concentrate on some independent variables that are hypothesized to have relationship with job satisfaction and job performance. Precisely, performance feedback, organizational justice including procedural justice and distributive justice are hypothesized to have positive impacts/roles on job satisfaction and job performance while task complexity is supposed to have negative impacts/roles on these both dependent variables. The purpose of this study is to examine impacts of performance feedback and roles of organizational justice and task complexity on job satisfaction and job performance in audit environment by proving the hypotheses. This study is carried out with some statistical methods by using SPSS program to analyze the relationship between independent variables and dependent variables.